Silver nanoparticle removal from drinking water: flocculation/sedimentation or filtration? - Lawler, Desmond F.; Mikelonis, Anne M.; Kim, Ijung; Lau, Boris L. T.; Youn, Sungmin (Water science & technology. Water supply, 2013)
Silver nanoparticles are used in a wide variety of consumer products and are therefore rapidly becoming ubiquitous in the natural environment; they can be expected to be found in the natural waters used as drinking water supplies. This research investigated whether such particles could be expected to be removed in conventional water treatment plants such as flocculation and filtration. Both flocculation and granular media filtration experiments with citrate-capped silver nanoparticles were performed at different ionic strengths and in the presence and absence of natural organic matter. The results were generally consistent with theories of particle destabilization that have been developed for larger particles (greater than 1 μm), suggesting that silver nanoparticles are likely to be removed in conventional treatment processes.